2018
DOI: 10.1371/journal.pone.0201952
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of pod-intravaginal rings delivering antiretroviral agents for HIV-1 prevention: Rectal drug exposure from vaginal dosing with tenofovir disoproxil fumarate, emtricitabine, and maraviroc

Abstract: BackgroundIntravaginal rings (IVRs) can deliver antiretroviral (ARV) agents for HIV pre-exposure prophylaxis (PrEP), theoretically overcoming adherence concerns associated with frequent dosing. However, topical vaginal ARV drug delivery has not simultaneously led to sufficient rectal drug exposure to likely protect from HIV infection as a result of receptive anal intercourse (RAI). Unprotected RAI has a higher risk of infection per sex act and, for women, also can be associated with vaginal exposure during a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…FTC and MVC concentrations found to be high in rectal fluids and provide high efficacy in HIV inhibition when the combination was delivered by IVR. Vaginal delivery of combined ART may allow coital‐independent protection from HIV acquisition though vaginal or rectal transmission . TFV, UC781 and dapivirine (DPV) with MVC showed that by inhibiting viral entry and reverse transcription, HIV transmission and infection can be prevented.…”
Section: Entry Inhibitormentioning
confidence: 99%
“…FTC and MVC concentrations found to be high in rectal fluids and provide high efficacy in HIV inhibition when the combination was delivered by IVR. Vaginal delivery of combined ART may allow coital‐independent protection from HIV acquisition though vaginal or rectal transmission . TFV, UC781 and dapivirine (DPV) with MVC showed that by inhibiting viral entry and reverse transcription, HIV transmission and infection can be prevented.…”
Section: Entry Inhibitormentioning
confidence: 99%
“…The use of insertable gels containing ARVs in clinical trials led to moderate success in the CAPRISA 004 study [7], and disappointing outcomes in the VOICE [6] and FACTS 001 trials, largely due to inconsistent adherence, especially among young women [6,7,9,10,60]. More recently, vaginal rings or infusions are being studied for the delivery of multiple anti-viral drugs, bNAbs or the viral entry inhibitor, 5P12-RANTES [61][62][63][64][65][66][67][68]. However, infusions will require the engagement of medical assistance and may not be easily accessible to women in different settings and geographic locations.…”
Section: Discussionmentioning
confidence: 99%
“…Rings containing DPV, TFV, TDF, MVC, or FTC alone or in combination using matrix, reservoir, and pod‐IVR configurations are also in clinical development. As mentioned, the pod‐IVR design achieved potentially protective concentrations of FTC and MVC in rectal fluid, possibly solving the two sites of infection‐one site of application problems . An MPT IVR combining DPV and levonorgestrel designed to last 90 days achieved safety and drug concentration targets in a 14‐day clinical study (MTN‐030/IPM041) .…”
Section: Next Generation Arv Prep Strategiesmentioning
confidence: 98%
“…79 In contrast to TFV and DPV, a multidrug pod-IVR demonstrated emtricitabine and maraviroc colorectal tissue concentrations greater than the in vitro protein-adjusted IC 90 in women. 80 Other ARVs in development may also diffuse more efficiently into vaginal and rectal tissue, potentially providing protection for the vagina and rectum with application of a vaginal product. Another alternative would be to develop a product suitable for dosing in both the vagina and the rectum to provide women the flexibility of protecting themselves wherever needed.…”
Section: Vaginal Product Underperformancementioning
confidence: 99%
See 1 more Smart Citation